Penguatan kompetensi perancangan mesin melalui pelatihan computer-aided design bagi mahasiswa dan alumni teknik mesin (Strengthening of machine design skills through the computer-aided design training for mechanical engineering students and alumni) - Irwansyah, I; Asbar, Asbar; Mubarak, Amir Zaki (Universitas Syiah Kuala, 2021)
The purpose of this service is to introduce and provide training on the use of Autodesk Inventor software to produce Computer-aided Design (CAD) based technical drawings according to the International Organization for Standardization (ISO). The method is carried out through theory, practice, and discussion, as well as completing machine design tasks independently and in groups. The training materials include working drawings, basic introduction to CAD, two-dimensional (2D) and three-dimensional (3D) drawing modeling, assembly, and presentation of 3D models. Evaluation of activities assessed refers to the readiness to complete the design task and the suitability of the drawings according to ISO standards. Based on the results of the basic level CAD training, there were achievements where participants had completed the technical drawing briefing material and completed the given design task. The design project task given requires mastery in terms of making 3D models from 2D sketch images, making layout drawings, making working drawings, and presenting them in a moving model presentation format. Successful completion of the task indicates that the participants understand and can operate the Autodesk Inventor software. In conclusion, this basic ability can be used as a provision for participants' self-development in the development and mastery of advanced CAD. This activity contributes based on the high interest in participating in training to the end and completing assignments and also has an indirect impact on the preparation of skilled CAD workers in the industry in Aceh.